Asthma prevalence & risk factor in children: Indian Scenario - D Sharad Gedam (International Journal of Medical Research and Review, 2014)
Various risk factors play a role in triggering allergic diseases among low-income households in developing countries. Indoor smoking, pets, overcrowding are some of the known factors for asthma.